Opportunities and Threats of Borderless Cultural Nationalism in National Security and Development of Nepal - Adhikari, Rishiram (Unity Journal, 2025)
Globalization, technological advancement, and mass migration change the concept of nationalism. Cultural nationalism creates both opportunities and threats to national security and development. Cultural nationalism, characterized by the sharing of cultural and religious values, is often depicted as surpassing national boundaries. In this light, relationships between Nepal, India, Pakistan, and Bhutan can be related to cultural nationalism because the people of these nations share the same culture and religion; however, they live in different nations. On the other hand, sharing common cultural and religious values helps these South Asian nations establish mutual understanding among nations at both the official and public levels. However, criminal activities also happened in the veil of culture, creating challenges on development and national security that Nepal has been facing for a long time. In this context, the study focused on the threat of borderless cultural nationalism. The main objective of this study is to analyze how borderless cultural nationalism affected maintaining national security and terrestrial unity in small nations like Nepal. The study followed a qualitative research design and used document analysis and in-depth interviews as data collection tools. The documents related to cultural nationalism were used as a source of secondary data. Primary data were collected through in-depth interviews. It is found that cultural nationalism creates both opportunities and threats to nation-building side by side, so strong and well-equipped security management and expertise-based diplomacy are needed to minimize the threats of cultural nationalism and develop its role in nation-building.